2021
DOI: 10.1111/cyt.13072
|View full text |Cite
|
Sign up to set email alerts
|

Technical aspects of the use of cytopathological specimens for diagnosis and predictive testing in malignant epithelial neoplasms of the lung

Abstract: Lung cancer is a leading cause of cancer mortality worldwide, 1 and for at least 50 years, primary pathological diagnosis has been based on small biopsies and cytopathological specimens. Until approximately 20 years ago, a simple binary categorisation of small cell and non-small cell lung carcinoma (NSCLC) was, in most cases, sufficient for diagnosis and treatment.However, recent years have seen a rapidly rising proportion of cases of NSCLC amenable to increasingly targeted therapy, initially based on the diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 133 publications
(294 reference statements)
0
12
0
Order By: Relevance
“…This is often overlooked, but Maddox and Smart outline how to make the most of the samples obtained and discuss practical issues such as specimen types, ROSE, handling processes and the vagaries of molecular testing. 3 Cytopathology samples have not enjoyed strong support from some sectors of the lung oncology community, with concerns raised about their suitability for biomarker profiling. Some of this reticence is the result of misconstruction of the fact that cytopathology-type samples are rarely, if ever, accepted in clinical trials when companion biomarkers are being developed.…”
Section: Editorialmentioning
confidence: 99%
See 1 more Smart Citation
“…This is often overlooked, but Maddox and Smart outline how to make the most of the samples obtained and discuss practical issues such as specimen types, ROSE, handling processes and the vagaries of molecular testing. 3 Cytopathology samples have not enjoyed strong support from some sectors of the lung oncology community, with concerns raised about their suitability for biomarker profiling. Some of this reticence is the result of misconstruction of the fact that cytopathology-type samples are rarely, if ever, accepted in clinical trials when companion biomarkers are being developed.…”
Section: Editorialmentioning
confidence: 99%
“…Suffice to say, cytopathology‐type samples can be perfectly adequate for molecular/biomarker profiling, provided, of course, that there is sufficient tumour content in the sample and that the sample has been handled and processed in a way that is permissive for all the testing that may be required. This is often overlooked, but Maddox and Smart outline how to make the most of the samples obtained and discuss practical issues such as specimen types, ROSE, handling processes and the vagaries of molecular testing 3 . Cytopathology samples have not enjoyed strong support from some sectors of the lung oncology community, with concerns raised about their suitability for biomarker profiling.…”
mentioning
confidence: 99%
“…Even surgically resectable adenocarcinomas are usually diagnosed by cytological specimens. It has been shown that cytology samples can be used for molecular testing to determine the most effective therapies 4 …”
Section: Introductionmentioning
confidence: 99%
“…The feasibility of non‐formalin fixed cytology specimens for RNA sequencing of lung adenocarcinomas has been shown in some recent studies 10,11 . Although residual cell pellets, smear slides and supernatants can be used for molecular testing, cell blocks are the most common source in daily practice 4,10,12–16 . However, Ramani, et al reported only a 45% success rate using cell blocks due to insufficient cellularity and/or suboptimal RNA quality 10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation